2018
DOI: 10.31489/2018ch4/41-47
|View full text |Cite
|
Sign up to set email alerts
|

Selective extraction of magnesium from asbestos-containing raw materials

Abstract: Selective extraction of magnesium from asbestos-containing raw materials In this work, great attention was paid to identifying the reasons for the absence of practically implemented technologies for processing chrysotile asbestos wastes and searching for new methods for treating wastes with the aim of obtaining magnesium and other useful products of commercial interest. A series of experiments with solutions of ammonium chloride of different concentrations was carried out to study the kinetics of magnesium lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our earlier calculations showed that the formation reactions of malachite and azurite with the participation of organic ligands are thermodynamically probable [12].…”
Section: Introductionmentioning
confidence: 97%
“…Our earlier calculations showed that the formation reactions of malachite and azurite with the participation of organic ligands are thermodynamically probable [12].…”
Section: Introductionmentioning
confidence: 97%